Crystal structure determination and refinement viaSIR2014. (1st February 2015) - Burla, Maria Cristina; Caliandro, Rocco; Carrozzini, Benedetta; Cascarano, Giovanni Luca; Cuocci, Corrado; Giacovazzo, Carmelo; Mallamo, Mariarosaria; Mazzone, Annamaria; Polidori, Giampiero
<x xml:space="preserve">Abstract</x> SIR2014 is the latest program of the SIR suite for crystal structure solution of small, medium and large structures. A variety of phasing algorithms have been implemented, both ab initio (standard or modern direct methods, Patterson techniques, Vive la Différence) and non‐ab initio (simulated annealing, molecular replacement). The program contains tools for crystal structure refinement and for the study of three‐dimensional electron‐density maps via suitable viewers.